Seismic Resilience and Sustainability: A Comparative Analysis of Steel and Reinforced Structures - Hasan Mostafaei; Morteza Ashoori Barmchi; Hadi Bahmani (Buildings)
This study presents a comprehensive comparative analysis of seismic resilience and sustainability between steel and reinforced concrete structures. With growing demand for environmentally responsible and disaster-resilient infrastructure, evaluating the life cycle performance of construction materials has become critical. Three building typologies—10-, 20-, and 30-story residential structures—are analyzed using a life cycle assessment (LCA), life cycle costing (LCC), and incremental dynamic analysis (IDA) to assess environmental, economic, and seismic performance. The results reveal that reinforced concrete structures tend to exert greater environmental impacts, particularly in categories such as carcinogenic emissions, ecotoxicity, and acidification, primarily due to cement production. Steel structures, while associated with higher energy consumption and mineral resource depletion, demonstrated superior seismic performance across all building heights, characterized by a greater level of ductility and collapse capacity. For instance, the 30-story reinforced concrete structure generated approximately 6.93 million kg CO2 eq, compared to 6.79 million kg CO2 eq for its steel counterpart. Steel structures, while associated with higher energy consumption and mineral resource depletion, demonstrated superior seismic performance across all building heights, sustaining up to a 15% greater spectral acceleration before collapse. Additionally, the LCC analysis showed that reinforced concrete is more cost-effective in high-rise construction, especially during the construction stage. These findings offer valuable insights for engineers and decision makers aiming to balance sustainability and structural performance in urban development.